Effects of Neuromuscular Training on Agility Performance in Elite Soccer Players - Zouhal, Hassane; Abderrahman, Abderraouf B.; Dupont, Gregory; Truptin, Pablo; Le Bris, Régis; Le Postec, Erwan; Sghaeir, Zouita; Brughelli, Matt; Granacher, Urs; Bideau, Benoit (Frontiers in Physiology, 2019)
Background: Agility in general and change-of-direction speed (CoD) in particular represent important performance determinants in elite soccer. Objectives: The objectives of this study were to determine the effects of a 6-week neuromuscular training program on agility performance, and to determine differences in movement times between the slower and faster turning directions in elite soccer players. Materials and Methods: Twenty male elite soccer players from the Stade Rennais Football Club (Ligue 1, France) participated in this study. The players were randomly assigned to a neuromuscular training group (NTG, n=10) or an active control (CG, n=10) according to their playing position. NTG participated in a 6-week, twice per week neuromuscular training program that included CoD, plyometric and dynamic stability exercises. Neuromuscular training replaced the regular warm-up program. Each training session lasted 30 minutes. CG continued their regular training program. Training volume was similar between groups. Before and after the intervention, the two groups performed a reactive agility test that included 180° left and right body rotations followed by a 5-m linear sprint. The weak side was defined as the left/right turning direction that produced slower overall movement times (MT). Reaction time (RT) was assessed and defined as the time from the first appearance of a visual stimulus until the athlete’s first movement. Results: No significant between-group baseline differences were observed for RT or MT. Significant group x time interactions were found for MT (p=0.012, effect size = 0.332, small) for the slower and faster directions (p=0.011, effect size = 0.627, moderate). Significant pre-to post improvements in MT were observed for NTG but not CG (p=0.011, effect size = 0.877, moderate). For NTG, post-hoc analyses revealed significant MT improvements for the slower (p=0.012, effect size = 0.897, moderate) and faster directions (p=0.017, effect size = 0.968, moderate). Conclusions: Our results illustrate that 6 weeks of neuromuscular training with 2 sessions per week included in the warm-up program, significantly enhanced agility performance in elite soccer players. Moreover, improvements were found on both sides during body rotations. Thus, practitioners are advised to focus their training programs on both turning directions.